The Proteasome System in Infection: Impact of β5 and LMP7 on Composition, Maturation and Quantity of Active Proteasome Complexes - Joeris, Thorsten (Public Library of Science, 2012)
Proteasomes are the major enzyme complexes for non-lysosomal protein degradation in eukaryotic cells. Mammals express two sets of catalytic subunits: the constitutive subunits β1, β2 and β5 and the immunosubunits LMP2 (β1i), MECL-1 (β2i) and LMP7 (β5i). The LMP7-propeptide (proLMP7) is required for optimal maturation of LMP2/MECL-1-containing precursors to mature immunoproteasomes, but can also mediate efficient integration into mixed proteasomes containing β1 and β2. In contrast, the β5-propeptide (proβ5) has been suggested to promote preferential integration into β1/β2-containing precursors, consequently favouring the formation of constitutive proteasomes. Here, we show that proβ5 predominantly promotes integration into LMP2/MECL-1-containing precursors in IFNγ-stimulated, LMP7-deficient cells and infected LMP7-deficient mice. This demonstrates that proβ5 does not direct preferential integration into β1/β2-containing precursors, but instead promotes the formation of mixed LMP2/MECL-1/β5 proteasomes under inflammatory conditions. Moreover, the propeptides substantially differ in their capacity to promote proteasome maturation, with proLMP7 showing a significantly higher chaperone activity as compared to proβ5. Increased efficiency of proteasome maturation mediated by proLMP7 is required for optimal MHC class I cell surface expression and is equally important as the catalytic activity of immunoproteasomes. Intriguingly, induction of LMP7 by infection not only results in rapid exchange of constitutive by immunosubunits, as previously suggested, but also increases the total proteasome abundance within the infected tissue. Hence our data identify a novel LMP7-dependend mechanism to enhance the activity of the proteasome system in infection, which is based on the high chaperone activity of proLMP7 and relies on accelerated maturation of active proteasome complexes.